1977
DOI: 10.1002/pssa.2210390209
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the crystal-to-glass transition on the local structure of semiconductors

Abstract: The influence of the crystal‐to‐glass transition on the local structure in semiconducting compounds and alloys such as As2S3, As2Se3, As2Te3, AsSI, AsSeI, As4Te5I2, As2Se3 · As2Te3, Ge15Te85, and As4Ge15Te81 is analysed by Mössbauer spectroscopy for nuclei of 125Te, 127I, 129Te(129I), and 119Sn and by measuring the chemical shift of the AsLα1 line. It is shown that for such compounds and alloys as As2Te3, As4Te5I2, Ge15Te85, As4Ge15Te81 the transition into the glassy state may take place only under conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
2
4
0
2
Order By: Relevance
“…Since, as mention above, the first two peaks consist of Se Se bond, the addition of Sn to the matrix primarily interact with the Se and break the Se Se bond; decreasing the number of Se Se bonds present in the alloy. These results were confirmed by Mössbauer spectroscopic study [16], from which it was concluded that Sn impurities in As-Se glasses interacted only with Se atoms and entered the glass as in SnSe 2 . A decrease in the value of bond angle is observed for x = 0 and 3 as seen in Table 2.…”
Section: Compositionsupporting
confidence: 76%
“…Since, as mention above, the first two peaks consist of Se Se bond, the addition of Sn to the matrix primarily interact with the Se and break the Se Se bond; decreasing the number of Se Se bonds present in the alloy. These results were confirmed by Mössbauer spectroscopic study [16], from which it was concluded that Sn impurities in As-Se glasses interacted only with Se atoms and entered the glass as in SnSe 2 . A decrease in the value of bond angle is observed for x = 0 and 3 as seen in Table 2.…”
Section: Compositionsupporting
confidence: 76%
“…Messbauer spectroscopy (MS) is an effective tool for detecting changes in the local environment of atoms and their electronic structure during amorphization of GeSbTe alloys. In particular, this has been demonstrated in works [16,17], in which the MS method on impurity atoms 119 Sn found that the amorphization of GeAsTe alloys (chemical analogues of (GeTe) x (Sb 2 Te 3 )) is accompanied by changes in the nearorder structure of germanium atoms.…”
Section: Introductionmentioning
confidence: 94%
“…However, apart from the work [18,19], as well as work [20], which shows the Messbauer spectra 121 Sb crystal compounds GeSb 2 Te 4 , Ge 2 Sb 2 Te 5 and GeSb 4 Te 7 , there are no Messbauer studies of ternary (GeTe) x (Sb 2 Te 3 ) compounds. In addition, we can mention the works [16,17,[21][22][23], in which the structure of glassy binary alloys Ge x Te 1−x was studied by the MS method on impurity atoms 119 Sn. In particular, it has been shown that the coordination and valence states of the germanium atoms change during amorphization [16,17,22,23], and the local structure of germanium sites in amorphous GexTe1-x (x < 0.2) [21] alloys has been described.…”
Section: Introductionmentioning
confidence: 99%
“…Отметим, что, изменение локальной структуры атомов германия в процессе аморфизации соединений GeSbTe (переход от двухвалентного шестикоординированного состояния к четырехвалентному четырехкоординированному состоянию) не является особенностью только соединений GeSbTe, поскольку аналогичный эффект наблюдался ранее и для сплавов системы Ge−As−Te [16,17].…”
Section: атомы германия в кристаллических пленках C-gesbteunclassified
“…Мессбауэровская спектроскопия (МС) является эффективным инструментом обнаружения изменений в локальном окружении атомов и их электронной структуры при аморфизации сплавов GeSbTe. В частности, это было продемонстрировано в работах [16,17], в которых методом МС на примесных атомах 119 Sn обнаружено, что аморфизация сплавов GeAsTe (химических аналогов сплавов (GeTe) x (Sb 2 Te 3 )) сопровождается изменением структуры ближнего порядка атомов германия.…”
Section: Introductionunclassified